On invariance of some properties of solutions under perturbation of a pulse system of differential equations - Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Sufficient conditions for the invariance of boundedness and stability properties of solutions under perturbation of a pulse system of differential equations are established.